Eksistensi Mata Kuliah Bahasa Indonesia dalam Mendukung Literasi Akademik Mahasiswa Kimia Universitas Negeri Medan - Nadin Manurung; Jakiah Jakiah; Anggun Mei Ivana; Joshua Podolski Manik; Nurul Azizah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This study aims to analyze the role of the Indonesian Language course in supporting the academic literacy of students in the Chemistry Program at the State University of Medan. This study uses a descriptive quantitative approach and involves 30 students who have taken the Indonesian Language course as respondents. Data were collected through an online questionnaire consisting of a Likert scale, multiple-choice questions, and essay questions. The results show that students have a positive perception of the Indonesian Language course with an average score of 16.23 out of a maximum score of 20. Most respondents stated that the Indonesian Language course supports the preparation of Chemistry research reports (90%), increases confidence in writing scientific articles (94%), helps in systematically presenting lab results (87%), and is considered an important foundational course for all study programs (84%). The material that was most helpful to students was scientific article texts (80%), while the greatest benefit was felt in the activity of writing lab reports (66.7%). Qualitative analysis indicates that the Indonesian Language course contributes to improving students’ scientific writing skills, use of standard language, and academic communication. Challenges still faced by students include the use of scientific language, the development of arguments, as well as citation techniques and the preparation of a bibliography. Thus, the Indonesian Language course plays a crucial role in supporting the academic literacy of Chemistry students and needs to be developed through more interactive and practical teaching methods.